Photophysics of Coumarin 460: Temperature Effect upon Fluorescence Lifetime and Non-Radiative Rate Parameter - Hussain, Ali A-K. (Iraqi Journal of Physics, 2002)
The temperature influence on the fluorescence lifetime, quantum yields and non-radiative rate parameter or coumarin 460 dye dissolved in methanol was investigated in the temperature range (160-300 k). A single photon counting technique was used or measuring the fluorescence decay curves. A noticeable decrease of the fluorescence lifetime with increasing the temperature was observed. The non-radiative activation energy of 10.57 K.J. mole-1 was measured by the help of Arrhenius plot.